2021
DOI: 10.3389/fphys.2021.616317
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Acetylcholine-Induced Relaxation of Aorta in Male UC Davis Type 2 Diabetes Mellitus (UCD-T2DM) Rats: Sex-Specific Responses

Abstract: Previous reports suggest that diabetes may differentially affect the vascular beds of females and males. The objectives of this study were to examine whether there were (1) sex differences in aortic function and (2) alterations in the relative contribution of endothelium-derived relaxing factors in modulating aortic reactivity in UC Davis Type 2 Diabetes Mellitus (UCD-T2DM) rats. Endothelium-dependent vasorelaxation (EDV) in response to acetylcholine (ACh) was measured in aortic rings before and after exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Mesenteric arterial vasodilatation was 24% less in male, but not in female, prediabetic UCD‐T2DM rats compared with age‐ and sex‐matched SD rats (Shaligram et al., 2020). In a subsequent ex vivo study looking at aortic endothelial function, it was found that acetylcholine‐induced vasodilatations were 17% greater in UCD‐T2DM males, but not females, compared with age‐ and sex‐matched SD rats (Akther et al., 2021). Both studies also reported changes to vascular muscle contractility, as evidenced by increased sensitivity and/or increased efficacy of the α 1 ‐adrenoceptor agonist phenylephrine (Akther et al., 2021; Shaligram et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mesenteric arterial vasodilatation was 24% less in male, but not in female, prediabetic UCD‐T2DM rats compared with age‐ and sex‐matched SD rats (Shaligram et al., 2020). In a subsequent ex vivo study looking at aortic endothelial function, it was found that acetylcholine‐induced vasodilatations were 17% greater in UCD‐T2DM males, but not females, compared with age‐ and sex‐matched SD rats (Akther et al., 2021). Both studies also reported changes to vascular muscle contractility, as evidenced by increased sensitivity and/or increased efficacy of the α 1 ‐adrenoceptor agonist phenylephrine (Akther et al., 2021; Shaligram et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In a subsequent ex vivo study looking at aortic endothelial function, it was found that acetylcholine‐induced vasodilatations were 17% greater in UCD‐T2DM males, but not females, compared with age‐ and sex‐matched SD rats (Akther et al., 2021). Both studies also reported changes to vascular muscle contractility, as evidenced by increased sensitivity and/or increased efficacy of the α 1 ‐adrenoceptor agonist phenylephrine (Akther et al., 2021; Shaligram et al., 2020). Together, the evidence suggests that the UCD‐T2DM rat, like the ZDSD rat, is useful for investigating the progressive vascular dysfunction in prediabetes to diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of CVD in premenopausal women is less than age-matched men, and female sex hormones, estrogen in particular, play a role in sex-specific cardiovascular protection in females (Barrett-Connor, 1994;Iorga et al, 2017). Several studies including ours suggest that diabetes affects male and female vascular beds differently (Witcher et al, 2010;Zhang et al, 2012;Lum-Naihe et al, 2017;Shaligram et al, 2020;Akther et al, 2021). Diabetes not only abrogates the female-specific cardiovascular protection, but also premenopausal women with diabetes experience higher CVD events than diabetic men (Peters et al, 2015;Castro, 2016), suggesting that hyperglycemia may overcome some of the beneficial effects of female sex hormones.…”
Section: Introductionmentioning
confidence: 84%